Severe Keratitis Caused by Pseudomonas aeruginosa Successfully Treated with Ceftazidime Associated with Acetazolamide. (26th April 2009) - Hue, Benoit; Doat, Marc; Renard, Gilles; Brandely, Marie-Laure; Chast, François
Abstract : Purpose . To report a case of microbial keratitis caused by Pseudomonas aeruginosa treated with a combination of acetazolamide and ceftazidime. Methods . Case report. Results . We report the case of a 17-year-old contact lens-wearing female who developed severe keratitis due to Pseudomonas aeruginosa temporarily healed with topical fortified antibiotic eye drops. After few days, the patient relapsed, and topical and intravenous ceftazidime were added. Concomitantly, oral administration of acetazolamide was prescribed. This carbonic anhydrase inhibitor was added to the antibiotic regimen in order to decrease the anterior chamber pH, and then, the ceftazidime ionization. By lowering the state of ionization of the antibiotic in the aqueous humor, its concentration was increased. This was confirmed by an improvement of the patient within few days and a rapid eradication of the infection. Conclusion . This is the first reported case of keratitis caused by P. aeruginosa successfully treated using acetazolamide as an enhancer of ceftazidime effectiveness.